LATE HISPANIC SIGILLATA FROM TERRONHA DE PINHOVELO (MACEDO DE CAVALEIROS, PORTUGAL) - Patrícia Magalhães, Ana (Rei Cretariae Romanae Fautorum Acta, 2024)
The research on Late Hispanic sigillata has been constantly omitted from studies of Roman pottery and for that reason it is still poorly known, which could also be due to the lack of study of this type of ceramics in its consumer sites. While in Spain there have been efforts to study the characteristics of the imports of this type of sigillata, in Portugal, especially in the North, where it should be represented better, in the available published studies of terra sigillata there are only some indications about the existence of these types of vessels. This setback could also be caused by the late identification of this sigillata type and the difficulty of finding good contexts to fix the chronology of this type of sigillata.